MEASUREMENT OF TRENDS OF SOME INFLUENTIAL VARIABLES: A COMPARISON BETWEEN BRAC BANK LTD. AND ISLAMI BANK BANGLADESH LTD. - Sina, Md. Abu; Sabur, Md. Abdus (International Journal of Research -GRANTHAALAYAH, 2017)
Banking sector is a fundamental element of a financial system of a country. Bangladesh is a developing country and its financial system is good and upward trend oriented. Islami Bank Bangladesh Limited (IBBL) and BRAC Bank Limited (BBL) are the two prospective banks in Bangladesh. The paper attempts to measure trends of some influential variables. Through Kaiser-Meyer-Olkin (KMO) and Bartlett’s test of Sphericity five influential variables are identified like net profit, investment/loans and advances, fixed assets, other assets and cash. All the variables show better position in IBBL than BBL. The researchers also have identified some problems in IBBL and BBL and recommended some suggestions for overcoming the problems.